Computer modelling of transition metal sulphide (FeS₂) - Mehlape, Mofuti Amos (My University, 2007)
The aim of this thesis is to study the structure and reactivity of FeS2 (pyrite).The transition metal sulphide, FeS2 crystallizes into cubic (pyrite) and orthorhombic (marcasite), is an important member of the sulphides minerals. The adjusted interatomic potentials were used for both energy minimization and molecular dynamics to study the surfaces and the bulk structure of pyrite. We also modelled the polymorph of pyrite, marcasite. With energy minimization we calculated the surface energies of the surfaces {100}, {110}, {111} and {210}. They revealed that {100} surface is the most stable surface. When we compared the surface energies calculated from the original potentials and the adjusted potentials, it is clear that the adjusted potentials improve the stability of the surfaces. It was also revealed that water stabilizes the surfaces, since the surface energies decreases when hydrated. Molecular dynamics (MD) was used to see the effect of temperature on the surfaces. To analyze our results we used the MD properties, namely, radial distribution functions (RDFs), diffusion coefficient and mean squared displacement (MSD). It was shown that as we increase the temperature both the bulk and the surfaces reach the molten phase. The melting point of the bulk is high than that of surfaces. Again molecular dynamics was used to study the nanocrystals of pyrite. We investigated the aggregation process of the pyrite nanoparticles. With the help of the RDF, it was revealed that the particles adopt a near amorphous structure when aggregated. We considered the effect of the crystal size on the solid/water interface. We modelled a pyrite nanoparticle in vacuum and immersed in water. The nanoparticle undergoes a phase change in vacuum, but in the presence of water, the pyrite structure was stabilized.
Thesis (M.Sc. (Physics)) -- University of Limpopo, 2007
Keywords: Molecular dynamics; Radial distribution functions; Transition metal sulfur compounds; Computer simulation